Workplace suspicion, knowledge hiding, and silence behavior: A double-moderated mediation model of knowledge-based psychological ownership and face consciousness - Wu, Mengying; Li, Wei; Zhang, Lei; Zhang, Chi; Zhou, Hanhui (Frontiers in Psychology, 2023)
Silence behavior (SB) is a common and influential phenomenon in organizations. Scholars have explored a lot of antecedents on silence behavior, but rarely from the perspective of colleagues. Based on conservation of resources theory and self-regulation theory, the study constructs a double-moderated mediating model to explore the relationship between workplace suspicion (WS) and silence behavior as well as its mechanism. This study conducts a three-wave questionnaire survey and adopts 303 valid pairs of samples from 23 companies in China to validate the research hypotheses. A confirmatory factor analysis in AMOS software and PROCESS bootstrapping program in SPSS are used in this study. Our findings indicate that: (1) workplace suspicion is positively correlated with silence behavior; (2) knowledge hiding (KH) mediates the relationship between workplace suspicion and silence behavior; (3) knowledge-based psychological ownership (KPO) moderates this mediating effect by strengthening the negative impact of workplace suspicion on knowledge hiding; (4) face consciousness (FC) moderates the mediating effect by weakening the positive impact of workplace suspicion on knowledge hiding. Managerial and practical implications, limitations, and research directions in future are discussed and offered.